Effects of coaching on medical student well-being and distress: a systematic review protocol - Colin West; Lauren Breslin; Liselotte Dyrbye; Cynthia Chelf (BMJ Open, 2023)
Introduction Medical students experience higher rates of distress and burnout compared with their age-similar peers overall. Coaching has been proposed as one means of combating distress and burnout within the medical profession. The purpose of this systematic review is to synthesise the current evidence on the effects of coaching interventions on medical student well-being, including engagement, resilience, quality of life, professional fulfilment and meaning in work and distress, including burnout, anxiety and depressive symptoms.Methods and analysis We will conduct a systematic review of interventional and observational comparative studies that assess the effects of coaching interventions on well-being, including engagement, resilience, quality of life, professional fulfilment and meaning in work and distress, including burnout, anxiety and depressive symptoms among undergraduate medical students internationally. We will search PubMed (MEDLINE), Embase (OVID), PsycINFO (OVID), Scopus, ERIC, Cochrane Database of Systematic Reviews (OVID) and Cochrane Central Register of Controlled Trials (OVID) from their respective inception dates using the following search terms: (medical students OR medical student OR undergraduate medical education) AND (coach OR coaching OR coaches). Studies in any language will be eligible. Studies that report one or more outcomes of distress or well-being among medical students who receive a coaching intervention will be included. Data on participant and intervention characteristics, outcomes and instruments used will be collected as well as quality/risk of bias assessments. Two reviewers will screen studies against the inclusion criteria and perform data extraction. We will conduct a narrative synthesis, with meta-analysis if evidence permits quantitative pooling of results. Heterogeneity of results across studies according to study design, learner level and study risk of bias will be evaluated, as well as publication bias.Ethics and dissemination Ethical approval is not required for this review. Results will be disseminated by publication in a scientific journal.PROSPERO registration number CRD42022322503.